A Multiparametric Method Based on Clinical and CT-Based Radiomics to Predict the Expression of p53 and VEGF in Patients With Spinal Giant Cell Tumor of Bone - Wang, Qizheng; Zhang, Yang; Zhang, Enlong; Xing, Xiaoying; Chen, Yongye; Nie, Ke; Yuan, Huishu; Su, Min-Ying; Lang, Ning (Frontiers in Oncology, 2022)
Purpose: This project aimed to assess the significance of vascular endothelial growth factor (VEGF) and p53 for predicting progression-free survival (PFS) in patients with spinal giant cell tumor of bone (GCTB), and to construct models for predicting these two biomarkers based on clinical and computer tomography (CT) radiomics to identify high-risk patients for improving treatment. Material and Methods: A retrospective study was performed from April 2009 to January 2019. A total of 80 patients with spinal GCTB who underwent surgery in our institution were identified. The VEGF and p53 expression, clinical and general imaging information were collected. Multivariate Cox regression models were used to verify the prognostic factors. The radiomics features were extracted from the regions of interest (ROIs) in pre-operative CT, and then important features were selected by the SVM to build classification models, evaluated by 10-fold cross-validation. The clinical variables were processed using the same method to build a conventional model for comparison. Results: The immunohistochemistry from 80 patients were obtained, 49 with high-VEGF and 31 with low-VEGF; 68 with wild-type p53, and 12 with mutant p53. P53 and VEGF were independent prognostic factor affecting PFS found in multivariate Cox regression analysis. For VEGF, the Spinal Instability Neoplastic Score (SINS) were greater in the high than low groups, p<0.001. For p53, SINS (p=0.030) and Enneking stage (p=0.017) were higher in mutant than wild-type groups. The VEGF radiomics model built using 3 features achieved an area under the curve (AUC) of 0.88, and the p53 radiomics model built using 4 features had an AUC of 0.79. The conventional model built using SINS, and Enneking stage had a slightly lower AUC of 0.81 for VEGF, and 0.72 for p53. Conclusion: P53 and VEGF are associated with prognosis in patients with spinal GCTB, and the radiomics analysis based on pre-operative CT provides a feasible method for evaluation of these two biomarkers, which may aid in choosing better management strategies.